PENGARUH KOMUNIKASI KESEHATAN SECARA LISAN DAN TULISAN TERHADAP PENGETAHUAN, SIKAP DAN KEBERSIHAN GIGI TIRUAN PARA PEMAKAI GIGI TIRUAN LEPASAN: INFLUENCE OF VERBAL AND WRITTEN COMMUNICATION ON KNOWLEDGE, ATTITUDE AND DENTURE HYGIENE OF THE REMOVABLE DENTURE USER - Surartono Dwiatmoko; Dewi Kristiana (Dentika: Dental Journal, 2011)
Oral hygiene of removable denture users is necessarily concerned, since it may support oral health completely. Removable denture users necessitated to clean their dentures in order to prevent food debris attach on the denture. One of the methods is to inform the users about how to clean removable denture and the communication built b etween dentist and the patient, and it may be accompanied by some aids such as leaflet. The purpose of this study was to know the influence of verbal and written communication by providing leaflet on the knowledge, attitude and denture hygiene of theremovable denture users , who ordered removable dentures at the Prostodontic Clinic in Dental Hospital Jember University. Total sample was 96 subjects, the research were patients who came to Dental Hospital Jember University for removable denture. The samples were divided into 2 groups, the first group received verbal and written communication (leaflet) a nd control group achieved only verbal communication. The communicator explained the methods of maintaining a removable denture. The results showed that there was a significant differences (p=0,00) o f the knowledge behavior between the two groups and the denture hygiene. In conclusion, there were significant differences on the knowledge, attitude and denture hygiene between verbal and written communication of the removable denture user.